Efeito do rotífero exótico Kellicottia bostoniensis (Rousselet, 1908) sobre os componentes da teia alimentar microbiana. - Oliveira, Felipe Rafael de (2018)
Species introduction can alter the structure and dynamics of biological communities and, therefore, understanding their feeding behavior and the effects that an exotic species can cause in the food webs configuration is pivotal. We aimed to experimentally investigate the effects of the potential invasive species Kellicottia bostoniensis on different components of the microbial food web, and to evaluate if the food preferences of this species change under different conditions of resource availability and interspecific interactions. We tested the hypothesis that the presence of K. bostoniensis would have direct and indirect effects on the different components of the planktonic food web. We designed three different experiments using prey size fractionation, each one composed of a control in the absence of K. bostoniensis and a treatment with the presence of this species. Results showed that K. bostoniensis caused direct effects on its main food items, the heterotrophic and autotrophic flagellates, whereas no evidence of indirect effects was observed on the base components of the microbial web food, such as heterotrophic bacteria and picophytoplankton. In addition, a negative effect of the exotic rotifer on ciliates was observed. Finally, we emphasize that the impact of K. bostoniensis on aquatic ecosystem may be quite harmful, since this specie can act as a sink of matter and energy to higher trophic levels.